2005
DOI: 10.1152/ajpregu.00147.2005
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and cognitive effects of grape polyphenols in estrogen-depleted, female, spontaneously hypertensive rats

Abstract: Both endogenous and dietary estrogens reduce hypertension and enhance cognitive abilities in estrogen-depleted female spontaneously hypertensive rats (SHR). Many of the beneficial effects of estrogens/phytoestrogens also appear to be provided by other polyphenols (e.g., proanthocyanidins) in grape seed, which lack appreciable estrogenic receptor binding. The present study tested the hypothesis that similar to phytoestrogens, proanthrocyanidins in grape seed polyphenols reduce salt-sensitive hypertension in you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 38 publications
1
53
0
Order By: Relevance
“…10) Proanthocyanidin is a kind of phenolic compound (oligonols are catechin-type monomers, dimmers and trimers, as well as oligomeric proanthocyanidins) present in plants, especially highly present in the grape seed, that has received attention recently. 11,12) Experimental and clinical studies have revealed that proanthocyanidin has antioxidant, antinociceptive, anti-emetic, and cardioprotective properties, without inducing significant toxicological effects. [13][14][15][16] In view of the above reports, we try to investigate whether proanthocyanidin has any effects on the activity of 5-HT 3 receptors.…”
Section: -Hydroxytryptamine (5-ht)mentioning
confidence: 99%
“…10) Proanthocyanidin is a kind of phenolic compound (oligonols are catechin-type monomers, dimmers and trimers, as well as oligomeric proanthocyanidins) present in plants, especially highly present in the grape seed, that has received attention recently. 11,12) Experimental and clinical studies have revealed that proanthocyanidin has antioxidant, antinociceptive, anti-emetic, and cardioprotective properties, without inducing significant toxicological effects. [13][14][15][16] In view of the above reports, we try to investigate whether proanthocyanidin has any effects on the activity of 5-HT 3 receptors.…”
Section: -Hydroxytryptamine (5-ht)mentioning
confidence: 99%
“…The superoxide anion scavenging activity of GSPE was stronger than vitamin C, vitamin E or any other antioxidant. 1) It has been reported to have protective effects on various cardiac disorders, correct dyslipidemia associated with high-fat diet, 2) decrease arterial pressure in estrogen-depleted female spontaneously hypertensive rats, 3) prevent diabetic nephropathy and neuropathy from progressing, 4,5) and most importantly, ameliorate atherosclerosis, 6) possibly attributed to its endothelial protective potential.…”
mentioning
confidence: 99%
“…Grape seed extract (GSE) is a rich botanical source of polyphenols (approximately 90% of which are procyanidins and 7% other polyphenol compounds) [52], and has become popular for the treatment and prevention of heart disease and other disorders. In vivo, the hypotensive effects of GSE were demonstrated in spontaneously hypertensive rats fed a 0.5% GSE-supplemented diet with basal (0.6%) or high (8.0%) NaCl, leading to a reduction in mean arterial pressure of 10 and 26 mmHg, respectively, compared with nonsupplemented groups [52].…”
Section: Grape Seed: Vitis Vinifera L (Vitaceae)mentioning
confidence: 99%
“…In vivo, the hypotensive effects of GSE were demonstrated in spontaneously hypertensive rats fed a 0.5% GSE-supplemented diet with basal (0.6%) or high (8.0%) NaCl, leading to a reduction in mean arterial pressure of 10 and 26 mmHg, respectively, compared with nonsupplemented groups [52].…”
Section: Grape Seed: Vitis Vinifera L (Vitaceae)mentioning
confidence: 99%